Ectodermal dysplasia associated with autoimmune disease. Issue 5 (May 1984) - Hung, S O; Patterson, A
Abstract : A case is reported of hereditary ectodermal dysplasia with corneal involvement associated with polyendocrinopathy and pernicious anaemia. The presence of autoantibodies to various endocrine organs and ocular tissues is confirmed. This suggests that ectodermal dysplasia may be an autoimmune disease.